Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1152/ajpcell.00356.2011
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of endothelial BK channels by heme oxygenase-derived carbon monoxide and caveolin-1

Abstract: A novel vasodilatory influence of endothelial cell (EC) large-conductance Ca(2+)-activated K(+) (BK) channels is present after in vivo exposure to chronic hypoxia (CH) and may exist in other pathological states. However, the mechanism of channel activation that results in altered vasoreactivity is unknown. Previously, we demonstrated that inhibition of either BK channels or heme oxygenase (HO) restores vasoconstrictor reactivity after CH. Additionally, administration of the scaffolding domain of caveolin (Cav)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
(88 reference statements)
0
20
0
Order By: Relevance
“…We have described differences in Ca 2ϩ sensitivity of BK Ca channels in EC and VSMC (23,24), directly demonstrating potential differences in regulation of BK Ca channels in these two cell types. Specifically, EC BK Ca channels display a greater Ca 2ϩ sensitivity despite the apparent lack of functional BK-␤1 subunits, and H 2 S may affect the moiety responsible for this difference.…”
Section: Discussionmentioning
confidence: 76%
“…We have described differences in Ca 2ϩ sensitivity of BK Ca channels in EC and VSMC (23,24), directly demonstrating potential differences in regulation of BK Ca channels in these two cell types. Specifically, EC BK Ca channels display a greater Ca 2ϩ sensitivity despite the apparent lack of functional BK-␤1 subunits, and H 2 S may affect the moiety responsible for this difference.…”
Section: Discussionmentioning
confidence: 76%
“…In several studies, it was shown that BK Ca channels are strongly activated by CORM-2 or CORM-3 [ 91 , 92 , 93 , 94 ] and that different regions that are unrelated to the heme binding motif (HBM) were implicated in this phenomenon [ 95 , 96 ]. Specifically, the stimulatory action of CORM-2 on BK Ca channels required the presence of an aspartic acid and two histidine residues (365 and 394) in the cytoplasmic RCK1 domain [ 96 ].…”
Section: Carbon Monoxidementioning
confidence: 99%
“…Although both HO-1 and HO-2 are primarily found in the endoplasmic reticulum (e.g., Tenhunen et al, 1968), there is now sufficient evidence that both enzymes can associate with Cav1 at the plasma membrane of mesengial (Jung et al, 2003) and endothelial cells . Further reports indicated that Cav1 is a competitive inhibitor for HO-1, identifying a minimum sequence required for binding (Taira et al, 2011) and possibly regulating activation of BKCa channels in endothelium (Riddle and Walker, 2012) [although this Cav1 interaction has yet to be detected in smooth muscle cells where the link between BK and CO was originally identified and well-described (Wang et al, 1997;Jaggar et al, 2002Jaggar et al, , 2005Xi et al, 2004)]. One report indicated that cytochrome P450 reductase is also associated with Cav1 (Jung et al, 2003), potentially forming a compartmentalized signaling microdomain for CO production.…”
Section: Signaling Microdomains In the Release Of Hydrogen Sulfidementioning
confidence: 99%